RELATIVE TOXICITY OF SELECTED ACARICIDES ON TWO SPOTTED SPIDER MITE (TETRANYCHUS URTICAE) OF BRINJAL - M. K. KAVYA; N. SRINIVASA; G. B. RAVI; A. S. VIDYASHREE (The Bioscan, 2015)
Relative toxicity of eleven commercially available newer acaricides was tested against two spotted spider mite, Tetranychus urticae (Koch) under laboratory condition. Abamectin was found most action ovicidal with the lowest LC50 value of 2.63 ppm having growth regulating activity among this Hexythiazox and Buprofezin, Hexythiazox was more toxic to eggs and other developmental stages. Abamectin and Fenpyroximate were more toxic to adult females, while HMO was least toxic (with LC50 values of 0.01, 1.91 and 424.10 ppm, respectively). All the acaricides tested under laboratory conditions were proved superior over control and Abamectin and Fenpyroximate were more toxic to eggs and adults with the lowest LC50 values compared to other acaricides.